EFFECTS OF P, F(O2) AND MG/FE RATIO ON DEHYDRATION MELTING OF MODEL METAGREYWACKES - Patino Douce A.E.; Beard Ja.S. (My University, 1996)
We present results of dehydration melting experiments [3–15 kbar, 810–950°C f(O2) ? QFM (quartz-fayalite-magetite) and ? Ni-NiO] on two Fe-rich mixtures of biotite (37%), plagioclase An38 (27%), quartz (34%) and ilmenite (2%), which differ only in their biotite compositions (mg-number 23 and 0.4). Dehydration melting of metagreywackes of constant modal composition generates a wide range of melt fractions, melt compositions and residual assemblages, through the combined effects of pressure, Fe/Mg ratio and f(O2). Crystallization of garnet is the chief control on melting behavior, and is limited by two reactions: (1) the breakdown of garnet + quartz to orthopyroxene + plagioclase at low P, and (2) the oxidation of garnet to magnetite + anorthite + quartz (?enstatite), which is sensitive to both f(O2) and P. Because of these reactions, melting of Mg-rich metagreywackes is rather insensitive to f(O2) but strongly sensitive to P; the converse is true for Fe-rich metagreywackes. Garnet crystallization requires that plagioclase break down incongruently, liberating albite. This increases the Na2O content of the melts and enhances melt production. Thus, melting of metagreywacke in a reducing deep-crustal environment (with garnet stable) would produce more, and more sodic, melt than would garnet-absent melting of the same source material in a relatively oxidizing, shallow-crustal environment.